If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(5w + -2) + -4(3w + -5) = w Reorder the terms: 3(-2 + 5w) + -4(3w + -5) = w (-2 * 3 + 5w * 3) + -4(3w + -5) = w (-6 + 15w) + -4(3w + -5) = w Reorder the terms: -6 + 15w + -4(-5 + 3w) = w -6 + 15w + (-5 * -4 + 3w * -4) = w -6 + 15w + (20 + -12w) = w Reorder the terms: -6 + 20 + 15w + -12w = w Combine like terms: -6 + 20 = 14 14 + 15w + -12w = w Combine like terms: 15w + -12w = 3w 14 + 3w = w Solving 14 + 3w = w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-1w' to each side of the equation. 14 + 3w + -1w = w + -1w Combine like terms: 3w + -1w = 2w 14 + 2w = w + -1w Combine like terms: w + -1w = 0 14 + 2w = 0 Add '-14' to each side of the equation. 14 + -14 + 2w = 0 + -14 Combine like terms: 14 + -14 = 0 0 + 2w = 0 + -14 2w = 0 + -14 Combine like terms: 0 + -14 = -14 2w = -14 Divide each side by '2'. w = -7 Simplifying w = -7
| 28-x+30-x+3x+x=40 | | -7+6.5(1+2.5s)=-16.5 | | (T+0.5)4=5 | | -6xy+6xy= | | X(2)=5(5) | | f(-2)=(4m-3)/(m-7) | | 2(x-5)=7-2x | | 3sinx-4cosx-2=0 | | .2(7-x)=4 | | 5-3x-(-4x+6)=-(8x+11)-(3x-10) | | 42.5/y=x | | 2=(3+x)+3(2) | | x^(-1/5)=(1/3) | | x^-1/5=1/3 | | 8x+41y+10=180 | | 2n/3=4 | | x-x+3x+x+30+28=40 | | 5h-7-3h=2(h-14) | | a^3-64= | | (2c+1)=(c-5) | | 4x^2+4y^2-16x+32y-20=0 | | (2c-1)=(c-5) | | 12y-18/2 | | 16x-3=68+13+4x | | 2x+4x+2x+1+5x-6=60 | | r/s=25 | | 9x+1=9(1)+2 | | (37b-8)-9(4b+4)=-2 | | 96.8639/883.3525= | | 1-0.4p=2 | | 3x-6=-7x-6 | | 1x+16+56=90 |